CANDU DAN MILITER KETERLIBATAN BADAN-BADAN PERJUANGAN DALAM PERDAGANGAN CANDU DI JAWA PADA MASA REVOLUSI - Julianto Ibrahim (Universitas Gadjah Mada, 2016)
During revolution era, Indonesian government used and traded opium for struggle funds. This decisionwas based on the fact that the social, economic and financial was shattered due to Japanese occupation.Whereas the government should provide substantial funds to pay the war operations, employeesalaries and soldiers, buy weapons of war, and pay representatives abroad. This paper constitutesas the result of historical studies, that is why it uses historical method and methodologies. Historicalmethod constitutes as a historian guidelines to find historical documents. Historian is like “handyman”who collects historical sources such as archives and documents in “warehouses” archives and libraries.When written sources are considered as not enough, then those will be held interviews with historicalactors involved directly or indirectly to the problem under study. Historical method constitutes aworks of historian from processing facts, explanations to the reconstruction of the results under study.Methodology provides the framework of thinking as historian, that is why, it needs to pay attentionto the concepts and theories in preparing the events of the past. This study is based on the methodfrom Ernst Bernheim, that are heuristic, criticism, auffassung and darstellung. Indonesian governmentfully managed and controlled the opium trade and circulation in Java. The management was led bythe Vice President Office assisted by two ministries, namely the Ministry of Finance and Ministry ofDefence Quartermaster Section. Under those two ministries, there was the Mayor Administrative Officeof Opium and Salt in Surakarta which coordinated major offices in several cities, especially in Kediriand Yogyakarta. The Administrative Office of Opium and Salt in Kediri stored raw opium. Then, rawopium was sent to processing factory in Wonosari and Beji Klaten. The cooked opium was sent to TheAdministrative Office of Opium and Drug in Yogyakarta or The Mayor Administrative Office of Opiumand Salt in Surakarta. This office in Surakarta authorized to issue raw opium to the struggle agencies tobe sold to the territory of republic, occupied Netherlands area or smuggled abroad.